2005
DOI: 10.1038/nature04139
|View full text |Cite
|
Sign up to set email alerts
|

Specification of astrocytes by bHLH protein SCL in a restricted region of the neural tube

Abstract: Astrocytes are the most abundant and functionally diverse glial population in the vertebrate central nervous system (CNS). However, the mechanisms underlying astrocyte specification are poorly understood. It is well established that cellular diversification of neurons in the embryo is generated by position-dependent extrinsic signals and combinatorial interactions of transcription factors that direct specific cell fates by suppressing alternative fates. It is unknown whether a comparable process determines emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
153
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(159 citation statements)
references
References 30 publications
6
153
0
Order By: Relevance
“…Lack of Olig2 expression in control cultures further supports astrocyte maturity and initial lack of progenitors. Indeed, whereas mature astrocytes lack Olig2 expression, this transcription factor is present in radial glial cells, glial-restricted progenitors and immature astrocytes (Marshall et al, 2005), and its expression has been shown to repress astrocytes differentiation (Fukuda et al, 2004;Muroyama et al, 2005). Serum starvation of the cultures prior growth factors addition, and possibly the repeated washes with ice-cold phosphate saline buffer initially designed to remove the microglial and oligodendroglial cells, which reside at the top of the cellular layer, might account for the lack of neural progenitors and stem cells in our astrocyte cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of Olig2 expression in control cultures further supports astrocyte maturity and initial lack of progenitors. Indeed, whereas mature astrocytes lack Olig2 expression, this transcription factor is present in radial glial cells, glial-restricted progenitors and immature astrocytes (Marshall et al, 2005), and its expression has been shown to repress astrocytes differentiation (Fukuda et al, 2004;Muroyama et al, 2005). Serum starvation of the cultures prior growth factors addition, and possibly the repeated washes with ice-cold phosphate saline buffer initially designed to remove the microglial and oligodendroglial cells, which reside at the top of the cellular layer, might account for the lack of neural progenitors and stem cells in our astrocyte cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Olig2 inhibits the differentiation of neural progenitors into astrocytes (Fukuda et al, 2004;Muroyama et al, 2005) and its expression is downregulated in vitro and in vivo in mature astrocytes (Fukuda et al, 2004;Marshall et al, 2005). Accordingly, a hardly detectable Olig2-immunoreactive signal was observed in control astrocytes (Figure 2g), whereas TGFa-treated cells exhibited a strong nuclear Olig2-immunoreactive signal (Figure 2h).…”
Section: Tgfa Dedifferentiates Astrocytesmentioning
confidence: 96%
“…R. Soc. B (2008) oligodendrocyte generation (Muroyama et al 2005). Thus, the opponent activities of Olig2 and Scl together with the Notch signalling pathway and other timing mechanisms may account for how distinct neuronal and glial cell types are generated in both a spatially and a temporally organized manner.…”
Section: Notch Signalling and The Transition Of Neural Progenitors Tomentioning
confidence: 99%
“…Insight into this process has recently been made through studies of the function of the bHLH protein Scl in the ventral spinal cord. Early in development, Scl is expressed by neural progenitors that give rise to a subset of V2 interneurons (Smith et al 2002;Muroyama et al 2005). However, at later times, the production of V2 interneurons ceases and Scl C cells transform into astrocyte progenitors (Muroyama et al 2005).…”
Section: Notch Signalling and The Transition Of Neural Progenitors Tomentioning
confidence: 99%
See 1 more Smart Citation